Long-Term In Vitro Culture Alters Gene Expression Pattern of Genes Involved in Ontological Groups Representing Cellular Processes - Zgórecka, Wiktoria; Kranc, Wiesława; Blatkiewicz, Małgorzata; Kamiński, Kacper; Farzaneh, Maryam; Bryja, Artur; Mozdziak, Paul; Antosik, Paweł; Zabel, Maciej; Podhorska-Okołów, Marzenna; Dzięgiel, Piotr; Kempisty, Bartosz; et al. (International journal of molecular sciences, 2024)
The oviduct provides an optimal environment for the final preparation, transport, and survival of gametes, the fertilization process, and early embryonic development. Most of the studies on reproduction are based on in vitro cell culture models because of the cell's accessibility. It creates opportunities to explore the complexity of directly linked processes between cells. Previous studies showed a significant expression of genes responsible for cell differentiation, maturation, and development during long-term porcine oviduct epithelial cells (POECs) in vitro culture. This study aimed at establishing the transcriptomic profile and comprehensive characteristics of porcine oviduct epithelial cell in vitro cultures, to compare changes in gene expression over time and deliver information about the expression pattern of genes highlighted in specific GO groups. The oviduct cells were collected after 7, 15, and 30 days of in vitro cultivation. The transcriptomic profile of gene expression was compared to the control group (cells collected after the first day). The expression of COL1A2 and LOX was enhanced, while FGFBP1, SERPINB2, and OVGP1 were downregulated at all selected intervals of cell culture in comparison to the 24-h control (p-value < 0.05). Adding new detailed information to the reproductive biology field about the diversified transcriptome profile in POECs may create new future possibilities in infertility treatments, including assisted reproductive technique (ART) programmes, and may be a valuable tool to investigate the potential role of oviduct cells in post-ovulation events.
Keywords: Fallopian Tubes; regulace genové exprese; Female; epitelové buňky; zvířata; vejcovody u zvířat; Cells, Cultured; Swine; Epithelial Cells; ženské pohlaví; Gene Expression Regulation; kultivované buňky; stanovení celkové genové exprese; transkriptom; Transcriptome; vejcovody; Animals; Gene Expression Profiling; Cell Culture Techniques; Oviducts; prasata; buněčné kultury